Race and ethnicity: Not factors in the prescribing of hydrocodone- and codeine-containing products in two pediatric emergency departments - Rees, MD, MPH, Chris A.; Bernhardt, PharmD, Melanie Brooke; Camp, PhD, Elizabeth A.; Lin, BA, Jessica S.; Chumpitazi, MD, MS, Corrie E. (Journal of Opioid Management, 2019)
Objective: To describe the prescription of hydrocodone-containing products (HCPs) and codeine-containing products (CCPs) by patient and provider race and ethnicity at two pediatric emergency departments (EDs) before and after the US Drug Enforcement Administration (DEA) rescheduling of HCPs in 2014. Design and setting: The authors performed a secondary analysis of data describing the prescription of HCPs and CCPs for 6 months before and after the DEA rescheduling of HCPs in two academic, urban pediatric EDs. Patients, participants: The authors included all children for whom race and ethnicity data were available and who were prescribed HCPs or CCPs at the time of discharge from the ED during a 12-month period (n = 1,246). The authors sent a three-question survey soliciting name, race, and ethnicity to all providers who prescribed an HCP or a CCP during the study period. Main outcome measures: Chi-square comparisons were made between the number of HCP and CCP prescriptions for primary ED diagnosis and patient ethnicity or race. The number of HCP and CCP prescriptions before and after the DEA rescheduling were compared to patient and provider race and ethnicity using the Breslow-Day test for homogeneity. Results: There were no significant differences in the number of HCP and CCP prescriptions between the pre- and post-DEA rescheduling periods across all racial and ethnic groups. When comparing the number of HCP and CCP prescriptions to patient race, Caucasian patients (84.4 percent) were prescribed more HCPs and CCPs than African Americans (15.6 percent) for abdominal pain (p value = 0.02). Non-Hispanic providers prescribed CCPs more often (n = 38, 55.2 percent) than Hispanic providers (n = 0, 0.0 percent) after DEA rescheduling (Breslow-Day p value = 0.01). Providers of all races wrote similar numbers of HCP and CCP prescriptions before and after the DEA rescheduling (Breslow-Day p value = 0.99). Conclusions: Pediatric patients of all races and ethnicities received fewer HCP prescriptions after the 2014 DEA rescheduling of HCPs. However, Caucasian patients were prescribed HCPs and CCPs for abdominal pain more frequently than African American patients. There were no significant differences in the number of prescriptions of HCPs and CCPs by provider race.